A comparison of immunohistochemistry and mass spectrometry for determining the amyloid fibril protein from formalin-fixed biopsy tissue. Issue 4 (30th January 2015) - Gilbertson, Janet A; Theis, Jason D; Vrana, Julie A; Lachmann, Helen; Wechalekar, Ashutosh; Whelan, Carol; Hawkins, Philip N; Dogan, Ahmet; Gillmore, Julian D
Abstract : Amyloidosis is caused by deposition in tissues of abnormal protein in a characteristic fibrillar form. There are many types of amyloidosis, classified according to the soluble protein precursor from which the amyloid fibrils are derived. Accurate identification of amyloid type is critical in every case since therapy for systemic amyloidosis is type specific. In ∼20–25% cases, however, immunohistochemistry (IHC) fails to prove the amyloid type and further tests are required. Laser microdissection and mass spectrometry (LDMS) is a powerful tool for identifying proteins from formalin-fixed paraffin-embedded tissues. We undertook a blinded comparison of IHC, performed at the UK National Amyloidosis Centre, and LDMS, performed at the Mayo Clinic, in 142 consecutive biopsy specimens from 38 different tissue types. There was 100% concordance between positive IHC and LDMS, and the latter increased diagnostic accuracy from 76% to 94%. LDMS in expert hands is a valuable tool for amyloid diagnosis.